EFEITO DA ESTAÇÃO DO ANO SOBRE A TAXA DE PRENHEZ DE RECEPTORAS SUBMETIDAS A TE (TRANSFERÊNCIA DE EMBRIÃO) - SILVA, Arianny Gonçalves1; DA SILVA, Aldair Félix; COSTA, Luan Carlos dos Santos; FILHO, Luiz Carlos Cesar da Costa; FERREIRA, Mariane Gabriela Cesar Ribeiro; STERZA, Fabiana de Andrade Melo (ANAIS DO ENIC, 2024)
-